Karakteristik Curah Hujan Monsunal Pada Periode ENSO dan IOD (Studi Kasus: Lampung, Surabaya dan Jayapura) - Sisca Ayu Renitasari; Supriyatno Widagdo; Rudi Siap Bintoro (Universitas Hang Tuah, 2023)
The variability of rainfall in the Indonesian region is strongly influenced by the ENSO and IOD phenomenon. The purpose of this study is to describe the characteristics of the ENSO and IOD phenomena over a period of 31 years, compare the characteristics of rainfall under normal conditions and characteristics due to ENSO and IOD phenomenon, and analyze the monsoon rain area (Lampung, Surabaya, Jayapura) which are more influenced by ENSO and IOD phenomenon. The results showed that in the first decade to the second decade the incidence of La Niña decreased by 3.4% and then increased in the last decade by 4.3%, as the dominant La Niña incidence in weak intensity has increased every decade. At the time of the IOD phenomenon in the first decade to the second decade there was an increase in Positive IOD of 15.2% and then an increase which tends to be drastic in the last decade by 27.2%. In the Lampung and Surabaya areas, when El Niño and Positive IOD occur, the beginning of the rainy season tended to come later, meaning the dry season was longer, which occurred from May to November. When La Niña and Negative IOD occurred, the rainy season began earlier in June to November and experiences the rainy season throughout the year. In the Jayapura area, rainfall tended to occur throughout the year during the ENSO and IOD phenomena. The influence caused